Konstruk Bahasa Dalam Tradisi Budaya Melayu Islam Kerinci (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
Language in the reality of society, affects the way speakers think and act. It also affects the social and cultural dynamics of society. The reciprocal influence of language and culture is inevitable. In the context of the Islamic Malay community of Kerinci, the influence of language and culture can be seen in the lives of the people. This is because the language in the cultural tradition of the Malay Islamic Kerinci society has been unified in all aspects of people's lives. To prove this, qualitative research logic is used and refined by two approaches, namely; The ethnographic approach is used to examine the religious life of the ethnic Malay community of Kerinci Islam from the point of view of religion, culture, and history. To see the changes and dynamics that occur in the Malay Islamic society of Kerinci, the approach to the concept of capital developed by Bourdieu is also used to reflect the dynamics of people's lives in the context of Islam and the traditions of the Malay Islamic society of Kerinci. The findings of this study cover aspects of the multicultural spectrum, the tahlilan tradition, and the language spectrum. These three things are evidence of the reciprocal influence of language on the Malay Islamic cultural tradition of Kerinci. The absorption of other languages ​​in the Malay Islamic Kerinci language affects the culture of the users of that language. The arrival of Islam with the concept of language has changed the lifestyle of the mystical community into a rational society, and still accommodates the local traditions of the Kerinci Islamic Malay community.